Reconhecimento em Axel Honneth - Cesco, Marcelo Lucas (My University, 2016)
The present work intends to investigate the foundations for Axel Honneth’s Recognition Theory. In order to reach our goal, the text is divided into two central parts. Firstly, we analytically present Hegel’s Jena Lectures, aiming to approach the origins of the concept “recognition” and its theoretical involvement in the honnethian development of a “fight for recognition”. Secondly, we present and analyze the honnethian arguments for an update of Hegelian concepts which have enabled a normative ethics reconstitution. Honneth’s comprehension of recognition experience allows us to revise the model for the occurrence of intersubjective relations of self-realization. Herein, we evince these relations according to three spheres of recognition, namely, Love, Rights and Solidarity and their forms of self-realization.
A presente dissertação tem como objetivo investigar as bases fundamentais da Teoria do Reconhecimento apresentada por Axel Honneth. Para cumprir tal intento o presente texto é dividido em duas partes centrais. Em um primeiro momento, nos dois primeiros capítulos, são apresentados de forma analítica os textos hegelianos do período de Jena, visando abordar as origens do conceito de reconhecimento e sua implicação teórica no desenvolvimento honnethiano de uma luta por reconhecimento. Em um segundo momento, no último capítulo, são apresentados e analisados os argumentos honnethianos de uma atualização dos conceitos hegelianos que possibilitariam, por sua vez, uma reconstrução de uma eticidade normativa. A forma como Honneth compreende a experiência do reconhecimento permite a ele rever o modelo de como ocorre às relações intersubjetivas de autorrealização. Aqui essas relações são demonstradas de acordo com as três esferas do reconhecimento, a saber, o Amor, o Direito e a Solidariedade e suas respectivas formas de autorrealização.
Keywords: Honneth, Axel, 1949-; Reconhecimento (Filosofia); Autorrealização; Recognition (Philosophy); Self-realization